Increasing The Digital Health Competency of Salatiga City Pharmacists in The Era of Digital Health Transformation - Hati, Anita Kumala; Ratnasari, Yunia; M.N.H, Paulina Ambar (Pharmaceutical Journal of Indonesia, 2024)
Background: The Indonesia Ministry of Health has established six pillars of health transformation, one of which is health technology transformation. Pharmacist as a professional  health care must have digital health competency to contribute to the success of digital health transformation in Indonesia. Objective: This research aims to analyze and improve the digital health competency of Salatiga city pharmacists. Method: This research is a quasi-experimental research with a one-group pretest-posttest design. The number of participants was 30 pharmacists from the city of Salatiga. Digital health competency levels were measured before and after training using the Public Health Informatics Competencies for Primary Health Care (PHIC4PHC) questionnaire instrument. Competency levels are presented as ordinal data so that the Wilcoxon test is used to determine differences before and after intervention. Result: Participants in this study consisted of 63% pharmacists at pharmacies, 20% Primary Clinic pharmacists, and 17% Community Health Center pharmacists. Participants were aged between 26 and 47 years old with a period of pharmacist practice between 4 and 22 years. Analysis of respondents' digital health competency level before training obtained results of 2% basic level, 27% understanding level, 43% fluent level, and 23% expert level. Meanwhile, after 2 weeks of respondents applying the results of digital health training, there was an increase in respondents' competency to 30% fluent level and 70% expert level. The pharmacist's health competency increased significantly (p-value< 0.05). 20 participants increased their competency level, and 10 participants did not change their competency level. Conclusion: Digital health training has been proven to significantly increase the digital health competency of Salatiga city pharmacists. Keywords: e-Health, Telepharmacy, Informatics, Pharmacists, competence